Fitlady Fitness / Nurul Deyanna Mahadi ... [et al.] - Mahadi, Nurul Deyanna; Roslan, Dk Nur Athirah; Jamirin, Nurul Nabilah; Comillis, Shaun Luey; Sabdin, Mohd Thobrani (2016)
Our business is basically to provide fitness centre for women only. The idea is to provide gym specifically for women as we all know that most gym was conquered by man. Plus, we see that many people especially women did not want to get mixed with man in the gym. Our fitness also offered Tae Bo which is the movement in martial arts such as kicking and punches. Tae Bo movement also can improve women self-defense skills. Therefore, we see an opportunity to build this business. This proposal contains detailed information in each categorized from administrative, marketing, operational and financial plan. We bring you how our company operates, who holding what position; who is our target market and most important is how much profit we gain. First of all, the Administrative Plan is the one of important component when open up a business. The administrative of business is interchangeable with the performance or management of business operations, also including important decision making. In the organization, the managers of administrator have these 'function' that were described by Henri Fayal as "the elements of administrative such as planning, organizing, leading and controlling. These elements will lead the business to achieve the company goals. Based on the Operational Plan, we are ensuring that our service which is the fitness must meet the specification of the customer need based on the quality and satisfaction in using our service. Besides that, Operational management also design the method of conversion of inputs such as materials, labor, proprietary information, into outputs like a goods, services, value-added products, that is most beneficial to the organization especially to this company. Operations management also attempt to balance costs with revenue to achieve the highest net operating profit possible. The crucial aspect in this operational plan is we need to ensure that this business must run effectively and efficiently. Other than that, our Marketing Plan is begin with the identification of specific customer needs and how the firm intended to fulfill them while generating an acceptable level of return. The most important things in our marketing plan are the market plan strategies, market competition, market plan budget, and also the marketing goal, if these all can be fulfill in the marketing plan absolutely our business will run well and have a high demand from the customer.